Backtrace [videorecording (DVD)] - Maples, Mike (Screenwriter); Guzman, Ryan, 1987-; Stallone, Sylvester; Modine, Matthew; Williams, Meadow, 1966-; McDonald, Christopher, 1955-; Egglesfield, Colin; Hull, Lydia; Olson, Tyler Jon; Rizzuto, Sergio; Temmel, Swen (Lionsgate, 2019)
After suffering a brain injury from a bank heist gone wrong, Macdonald develops amnesia and is put into a prison psychiatric ward. Following his seventh year of evaluation, he is coerced by an inmate and a ward doctor to break out of prison and injected with a serum that forces him to relive the life he's forgotten. Macdonald must now elude a local detective, a tough FBI agent, and the drug's dangerous side effects in order to recover the stolen money.